2020
DOI: 10.1097/ico.0000000000002394
|View full text |Cite
|
Sign up to set email alerts
|

Sutureless Femtosecond Laser–Assisted Anterior Lamellar Keratoplasty Using a Bioengineered Cornea as a Viable Alternative to Human Donor Transplantation for Superficial Corneal Opacities

Abstract: Purpose: To evaluate the safety and efficacy of a bioengineered corneal implant using femtosecond laser–assisted anterior lamellar keratoplasty for superficial corneal opacities. Methods: Six eyes of 6 consecutive patients with superficial corneal stromal opacities involving <220 μm owing to various pathologies were included in the study. Preoperatively, all patients underwent anterior segment optical coherence tomography (Visante; Carl Zeiss Meditec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…A summary of recent clinical and preclinical studies of corneal bioengineering technologies is given in Supplementary Table 4. Most clinical studies, while having achieved significant advances in biomaterial properties, have addressed relatively rare causes of corneal blindness such as chemical burns 54,55 , infections [55][56][57][58] , ulcers 59 or high-risk cases 54,55 with the goal to stabilize the condition and avoid blindness, but not to optimize vision. Only two clinical studies to date have addressed keratoconus, a condition that impairs millions globally, aiming to provide vision gains comparable to standard PK or DALK.…”
Section: Discussionmentioning
confidence: 99%
“…A summary of recent clinical and preclinical studies of corneal bioengineering technologies is given in Supplementary Table 4. Most clinical studies, while having achieved significant advances in biomaterial properties, have addressed relatively rare causes of corneal blindness such as chemical burns 54,55 , infections [55][56][57][58] , ulcers 59 or high-risk cases 54,55 with the goal to stabilize the condition and avoid blindness, but not to optimize vision. Only two clinical studies to date have addressed keratoconus, a condition that impairs millions globally, aiming to provide vision gains comparable to standard PK or DALK.…”
Section: Discussionmentioning
confidence: 99%
“…To overcome the challenges of the recombinant collagen-based implant, the same group at Linköping University partnered with Farabi Eye Hospital in Tehran and All India Institute of Medical Sciences in New Delhi to develop a porcine-derived collagen type I implant to treat anterior stromal opacities. Their first-in-human trial in six patients demonstrated promising results with an improvement in mean BCVA to 0.26 logMAR, a decrease in mean cylinder by 1.0D, and an increase in mean stromal thickness by 47 μm postoperatively [39]. Five out of six patients had no complications at 1 year; one had a small area of melt that was managed successfully without a change in BCVA.…”
Section: Stromal Therapiesmentioning
confidence: 99%
“…[ 46 ] In 2020, Khodaparast et al . [ 48 ] demonstrated that FSL-assisted ALK using a bioengineered collagen corneal implant resulted in improved BCVA and astigmatism in 6 eyes with superficial corneal opacities, although the corneal implant was removed due to collagen melting in one eye. These results suggest that FSL can be a viable tool for the development of novel modified techniques of ALK.…”
Section: Femtosecond Laser-assisted Anterior Lamellar Keratoplastymentioning
confidence: 99%